Cost benefit analysis of extensive green roofs under tropic humid conditions in Villahermosa, Mexico - de la Cruz-Uribe, Adriana; Jesús-Castañeda, Miguel Ángel; Bolívar-Fuentes, Rosa Cristina; Laines-Canepa, José Ramón; Hernández-Barajas, José Roberto (Ecosistemas y Recursos Agropecuarios, 2023)
The objective was to analyze the profitability of the project for the installation of extensive green roofs on houses located in a humid tropical climate, considering the effect of various parameters on the benefit-cost ratio and the payback period of the investment. The environmental benefits were estimated from the life cycle analysis, while the unit cost analysis allowed determining the effect of material availability on installation costs. The analysis monetized two environmental benefits: electricity savings and carbon sequestration, based on the net present value of installation, maintenance, dismantling and disposal costs. The benefit-cost ratio was found to range from 1.1 to 3.8 with payback periods of 3.4 to 8.9 years, depending on the availability of materials, economic indicators, maintenance actions and the potential reward with carbon credits to the owner.